Clinical Data and Laboratory Tests on Covid-19 Patients in Six (6) Hospitals in 2021 - Sugiyanto, Zaenal; Sanaprila, Rahesti; Sucipto, Didi; Zabrina; Yusnita, Ine; Lu’luatun, Laila; Alfara, Yunika (Health Science UDINUS, 2024)
At the beginning of 2021, the hospital was still treating Covid-19 patients. To establish a diagnosis of Covid-19, we still use PCR and rapid tests and other laboratory tests. The purpose of this study was to explain patient clinical data and laboratory test results in Covid-19 patients. This research method is descriptive research with research instruments in the form of observation guidelines in the form of a check list with medical record document data sources from 6 hospitals in the Central Java region and the data will be processed descriptively. There were 81 patients with hypertension, 41 patients with tachycardia, 41 patients with tachypnea, 105 patients with moderate illness, 35 patients with severe illness and 3 patients in critical condition. Most of the PCR test results were positive, there were 400 patients. the majority of positive PCR examination results were 400 patients, most of the X-Ray Thorax examination results had abnormalities in 146 patients, There were 24 patients with results of oxygen saturation examination with mild - moderate hypoxia results and 2 people with severe hypoxia, There were 138 patients receiving electrolyte injections or infusions and 99 patients receiving Continous Invasive Mechanical Ventilation for 46 consecutive Hours or More, There were 3 laboratory examination results with mostly abnormal results, namely: C-Reactive Protein (CRP) was present 117 patients were abnormal, SGOT 99 patients were abnormal and SGPT 95 patients were abnormal.